The use of modern refractory materials for the use of gate devices - Unaspekov, Берикбай; Sarsekeyeva, Гульнар; Konarbaeva, Жанылган; Abdrasilov, Дулат (Рroblems of engineering and professional education, 2023)
The composition of fire-resistant, up-to-date building materials is considered and analyzed in the article.